2002
DOI: 10.1177/109830070200400203
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Children with Autism to Prefer Books or Toys Over Stereotypy or Passivity

Abstract: Two experiments were conducted with 4 students with autism to test the relationship between either toys or books as conditioned reinforcers for observing or playing and their effect on stereotypy and passivity. Experiment 1 consisted of a single preschool student who emitted frequent intervals of passive behavior and infrequent intervals of looking at books in a free play setting. After systematic training sessions involving pairings of reinforcers with looking at books, he engaged in looking at books signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 13 publications
7
56
0
2
Order By: Relevance
“…Psycho-behavioural interventions, especially those incorporating differential reinforcement (Braithwaite & Richdale, 2000;Nuzzolo-Gomez et al, 2002) and antecedent manipulations such as social stories (Scattone et al, 2002), have been found to be effective for reducing behaviour problems in children with ASD. Future research might assess whether, by reducing CBP, psycho-behavioural interventions are also beneficial for improving caregivers' psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Psycho-behavioural interventions, especially those incorporating differential reinforcement (Braithwaite & Richdale, 2000;Nuzzolo-Gomez et al, 2002) and antecedent manipulations such as social stories (Scattone et al, 2002), have been found to be effective for reducing behaviour problems in children with ASD. Future research might assess whether, by reducing CBP, psycho-behavioural interventions are also beneficial for improving caregivers' psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…also causes myriad difficulties for individuals with autism. Because of its odd and, for some individuals, noisy nature, repetitive motor behavior can create social stigma for students with autism and may further reduce opportunities for interaction with peers (Durand and Carr 1987), can prevent some students from being included in general education settings, and may interfere with students' ability to attend to and engage in academic instruction (Koegel and Covert 1972) and toy play (Koegel et al 1974;Nuzzolo-Gomez et al 2002). Accurate performance of learned tasks may also suffer when a child with autism engages in motor stereotypies (Morrison and Rosales-Ruiz 1997).…”
mentioning
confidence: 96%
“…If the participant did not select either visual stimuli, auditory stimuli, or both for at least 70 % of two of three assessment sessions, it was concluded that the stimuli did not function as conditioned reinforcers, and a stimulus pairing procedure (Greer, Becker, Saxe, and Mirabella 1985;Greer et al 1973aGreer et al , b, 2011aGreer, Dorow, and Randall 1974;Longano and Greer 2006;Nuzzolo-Gomez et al 2002;Tsai and Greer 2006) was implemented to condition either visual or spoken auditory stimuli as reinforcers.…”
Section: Preference Assessment For Spoken Words and Visual Stimulimentioning
confidence: 99%